The Meek Inherit the Earth - James D. Stone (Akademisk Kvarter, 2011)
In The Meek Inherit the Earth: Celebrating the End of American Power in Mars Attacks!, James Stone suggests that Mars Attacks, besides celebrating the aesthetics of alien invasion films, differs from other alien invasion films in the sense that while most Hollywood movies belonging to this group demonstrate U.S. strength and ingenuity, Mars Attacks! goes against the grain by refusing the general pro-American tone and foregrounding America's weaknesses; the film mischievously hints that the fall of the U.S. would be no tragedy, but an occasion for celebration.